Factors associated with combined hand and foot eczema. (15th November 2016) - Agner, T.; Aalto‐Korte, K.; Andersen, K.E.; Foti, C.; Gimenéz‐Arnau, A.; Goncalo, M.; Goossens, A.; Le Coz, C.; Diepgen, T.L.
Abstract: Background: As for hand eczema, the aetiology of foot eczema is multifactorial and not very well understood. The aim of the present study was to identify factors associated with foot eczema in a cohort of hand eczema patients being classified into different subgroups. Methods: Associations between foot and hand eczema were studied in a cross‐sectional design in a cohort of hand eczema patients. Consecutive patients were recruited from nine different European Centres during the period October 2011–September 2012. Data on demographic factors, presence of foot eczema, hand eczema duration and severity, and whether the hand eczema was work‐related or not were available, as well as patch‐test results. Results: Of a total of 427 hand eczema patients identified, information on foot eczema was available in 419 patients who were included in the present study. A total of 125 patients (29.8%) had concomitant foot and hand eczema. It was found more often in association with hyperkeratotic hand eczema ( P = 0.007) and was less often associated with irritant hand eczema ( P < 0.001). However, foot eczema was nevertheless found in 18% of patient with irritant hand eczema and in 25% of patients with occupational hand eczema. Combined foot and hand eczema was associated with more severe and long‐standing hand eczema ( P < 0.001 and P = 0.004, respectively). Contact allergy was found in 51.8% with no difference between patients with combined foot and hand eczema and patients with hand eczema only. Conclusion: Occurrence of combined foot and hand eczema is a common finding and not restricted to endogenous hand eczema.